EZH2/EHMT2 Histone Methyltransferases Inhibit the Transcription of DLX5 and Promote the Transformation of Myelodysplastic Syndrome to Acute Myeloid Leukemia - Zheng, Zhuanzhen; Li, Ling; Li, Guoxia; Zhang, Yaofang; Dong, Chunxia; Ren, Fanggang; Chen, Wenliang; Ma, Yanping (Frontiers in Cell and Developmental Biology, 2021)
Myelodysplastic syndrome (MDS) is characterized by clonal hematopoiesis and impaired differentiation, and may develop to acute myeloid leukemia (AML). We explored the mechanism of histone methyltransferase EZH2/EHMT2 during the transformation of MDS into AML. Expression of EZH2/EHMT2 in patients and in NHD13 mice was detected. EZH2 and EHMT2 were silenced or overexpressed in SKM-1 cells. The cell proliferation and cycle were evaluated. Levels of DLX5, H3K27me3, and H3K9me2 in SKM-1 cells were detected. Binding of DLX5 promoter region to H3K27me3 and H3K9me2 was examined. Levels of H3K27me3/H3K9me2 were decreased by EZH2/EHMT2 inhibitor (EPZ-6438/BIX-01294), and changes of DLX5 expression and cell proliferation were observed. EZH2 was poorly expressed in MDS patients but highly expressed in MDS-AML patients. EHMT2 was promoted in both MDS and MDS-AML patients. EZH2 expression was reduced and EHMT2 expression was promoted in NHD13 mice. NHD13 mice with overexpressing EZH2 or EHMT2 transformed into AML more quickly. Intervention of EZH2 or EHMT2 inhibited SKM-1 cell proliferation and promoted DLX5 expression. Both silencing EZH1 and EZH2 in SKM-1 cells, the H3K27me3 level was decreased. EZH2 silencing repressed the proliferation of SKM-1 cells. Transcription level of DLX5 in SKM-1 cells was inhibited by H3K27me3 and H3K9me2. Enhanced DLX5 repressed SKM-1 cell proliferation. In conclusion, EZH2/EHMT2 catalyzed H3K27me3/H3K9me2 to inhibit the transcription of DLX5, thus promoting the transformation from MDS to AML.